2013
DOI: 10.3389/fphys.2013.00185
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential and cancer progression

Abstract: Membrane potential (Vm), the voltage across the plasma membrane, arises because of the presence of different ion channels/transporters with specific ion selectivity and permeability. Vm is a key biophysical signal in non-excitable cells, modulating important cellular activities, such as proliferation and differentiation. Therefore, the multiplicities of various ion channels/transporters expressed on different cells are finely tuned in order to regulate the Vm. It is well-established that cancer cells possess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
558
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(577 citation statements)
references
References 136 publications
15
558
1
3
Order By: Relevance
“…As discussed earlier, even though the chondrocyte is a nonexcitable cell type, RMP acts as a key biophysical signal modulating important activities such as volume regulation, proliferation, and differentiation [30]. To identify what roles VDCCs may play in the regulation of chondrocyte proliferation and RMP, several studies have been conducted.…”
Section: Vdcc Inhibitors Influence Proliferation and Resting Membranementioning
confidence: 99%
“…As discussed earlier, even though the chondrocyte is a nonexcitable cell type, RMP acts as a key biophysical signal modulating important activities such as volume regulation, proliferation, and differentiation [30]. To identify what roles VDCCs may play in the regulation of chondrocyte proliferation and RMP, several studies have been conducted.…”
Section: Vdcc Inhibitors Influence Proliferation and Resting Membranementioning
confidence: 99%
“…Several theories correlating cancerous cells to depolarised voltage membrane potential (Vmem) values have been discussed in the literature [17,18]. Typical membrane potential values for healthy tissue range between -10mV to -90mV as shown in figure 5 [17,18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Several theories correlating cancerous cells to depolarised voltage membrane potential (Vmem) values have been discussed in the literature [17,18]. Typical membrane potential values for healthy tissue range between -10mV to -90mV as shown in figure 5 [17,18,19]. It can be seen that tumour cells and certain non-tumour cells such as proliferating fibroblasts and 3T3 cells possess lower membrane potential values; hence further research has suggested that ion channels/transporters such as Na+, Ca2+, K+, and Cl-(Sodium Ion, Calcium Ion, Potassium ion and Chlorine ion respectively) are contributing 10 factors to cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the more hyperpolarized resting membrane potential in differentiated cell types such as neurons or cardiomyocytes (60 to 80 mV), rapidly proliferating embryonic cells, stem cells, or cancer cell are in general more depolarized, with a resting membrane potential at 20 to 40 mV (Yang and Brackenbury, 2013). Therefore, one classical hypothesis is that membrane depolarization itself plays a functional role in tumor initiation or progression (Fig.…”
Section: Potassium Channel In Proliferation and Tumor Growthmentioning
confidence: 99%